Psychological States of Rural Area’s Children During Covid-19 Pandemic - Hon, Kai Yee; Ezzah Nurhazimah Husin; Norafifah Bali; Wanda Kiyah George Albert (Atlantis Press, 2021)
As the coronavirus (COVID-19) pandemic sweeps across the world, it has a profound effect on human psychological and daily life. However, fewer studies are focusing on children’s psychological states. The purpose of the present study aimed to examine the children’s psychological state and their emotions during the crisis of COVID-19. There were 14 children aged 7-12 years living in the rural areas in Sabah were recruited. By using the Collage Life Story Elicitation Technique (CLET), the thematic analysis indicated that a minority of the children expressed concern, anxiety, and gloomy verbally and non-verbally. Surprisingly, most of them accepted the new norms implemented by the Government, for instance, they understand that they must wear a face mask whenever they are outing and practice proper hygiene even though they are living in a rural area. The output of the present study reflected the children’s awareness of the coronavirus pandemic and adults are playing a vital role to ensure the wellbeing and welfare of the children.